Motivational factors impacting rural community participation in community-based tourism enterprise in Lenggong Valley, Malaysia. Issue 7 (2nd July 2020) - Jaafar, Mastura; Md Noor, Shuhaida; Mohamad, Diana; Jalali, Alireza; Hashim, Jariyah Binti
ABSTRACT: This study investigates factors motivating the participation of rural residents of Lenggong Valley, Malaysia, in community-based tourism enterprises (CBTEs). We used observation and focus group discussions to gain insights into the cognitive evaluation and social capital dimensions of local residents' participation in CBTEs. Observations were made of 32 participants during their CBTE initiation, while 15 participants contributed to focus group discussions 12-months later. The findings suggest that self-determination and perceived competence were integral to residents' continuous involvement and commitment in the CBTE project. We also found that strong social networks, trust in external groups, mutual cooperation, and shared goals were significant motivational factors for residents to participate in the project.